A soil organic carbon indexing and measurement system - Prout, Jonah M. (Cranfield University, 2021)
Soil organic carbon (SOC) is an important component of soils for the various goods and services that soils perform. But SOC stocks have declined significantly in soils around the world over many years due to poor land management. To enable land managers and policy makers to manage SOC better, simple guideline values and measures of SOC concentration are needed. An index based on the SOC to clay concentration ratio as related to soil structural conditions was tested for soils across England and Wales using data from the National Soil Inventory (NSI). Threshold values of SOC/clay equal to 1/8, 1/10 and 1/13 indicated Very Good, Good, Moderate and Degraded levels of SOC. Land use was a driver of SOC/clay ratio, with 38% of arable soils classed as Degraded compared with < 7% of permanent grass or woodland soils. To examine how SOC/clay ratios have been changing over time, I analysed data from resampled sites in the NSI (mean interval of 15 years). The Very Good class was particularly vulnerable to losses compared with other classes. This finding agrees with SOC protection being limited by soil clay concentration. Long-term experiments on soils of contrasting clay concentration showed that the index was sensitive to management activities. In further work I explored the use of dry soil spectral analysis to measure SOC and clay concentrations. I compared dry spectral and conventional wet laboratory analyses of soils in the NSI and in the US National Soil Survey Center-Kellogg Soil Survey Laboratory spectral library (NSSC-KSSL). The NSSC-KSSL results, and to a lesser extent the NSI results (which used older, less-accurate wet laboratory analyses), showed that the technique is suitable for assigning soils to Very Good, Degraded, or Good/Moderate ranges. The index provides quantitative guideline concentrations for SOC with a functional basis and scope for rapid assessment.
Keywords: Land use; clay concentration; soil structure; soil organic matter; long-term experiments; national soil inventory; soil monitoring; MIR spectral library